Evidence on Training and Career Paths : Human Capital, Information and Incentives - Eduardo Melero (Institute for the Study of Labor (IZA), 2004)
In this paper, I analyse the relationship between job-related training and career progress of workers. Most theories of career paths and task assignment rely on human capital accumulation. Therefore, it seems natural to start assessing the empirical validity of such theories by analysing the effect of training on the career progress of an individual. I use the sample of workers from twelve waves of the BHPS (1991-2002) to study the impact of training over the probability of making a career-improving move, using both between-groups and within-group panel data estimators. I find that job-related training received by female workers boosts significantly their chances of being promoted in the next future, while leaving virtually unaffected the chances of male workers. Then, I investigate how do training and promotion jointly influence wage growth. The results show that their interaction is, if any, positive. Additional evidence confirms that the career path of female workers seem to be importantly affected by the market value of their human capital, while that of men might be more affected by the role of promotion systems as mechanisms devised to provide incentives.
Keywords: J64; J24; M53; M52; M51; 330; human capital; training; task allocation; careers; internal labour markets; Betriebliche Bildungsarbeit; Bildungsinvestition; Interner Arbeitsmarkt; Erwerbsverlauf; Geschlecht; Schätzung; Grossbritannien